2019
DOI: 10.3389/fnins.2018.01006
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Protects Mice Brain From Apoptosis in Traumatic Brain Injury Model Through Activation of Autophagy

Abstract: Autophagy is associated with secondary injury following traumatic brain injury (TBI) and is expected to be a therapeutic target. Baicalin, a neuroprotective agent, has been proven to exert multi-functional bioactive effects in brain injury diseases. However, it is unknown if Baicalin influences autophagy after TBI. In the present study, we aimed to explore the effects that Baicalin had on TBI in a mice model, focusing on autophagy as a potential mechanism. We found that Baicalin administration significantly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…35 Meanwhile, baicalin has been shown to induce autophagy in a variety of cell types including hepatocellular carcinoma cells, 26,36 breast cancer cells, 37 and even mice brain. 38 In this context, we examined whether baicalin could protect fibroblast cells against UVB radiation via reducing apoptosis and inducing autophagy, and explored if the underlying mechanism of autophagy induction is via activation of AMPK and downregulation of mTOR. 13 In the present study, we found that baicalin increased cell viability ( Figure 1A) and suppressed apoptosis (Figure 2A and B) of human fibroblast cells induced by UVB at 600 J/m 2 , the dose level high enough to caused fibroblast cells to undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…35 Meanwhile, baicalin has been shown to induce autophagy in a variety of cell types including hepatocellular carcinoma cells, 26,36 breast cancer cells, 37 and even mice brain. 38 In this context, we examined whether baicalin could protect fibroblast cells against UVB radiation via reducing apoptosis and inducing autophagy, and explored if the underlying mechanism of autophagy induction is via activation of AMPK and downregulation of mTOR. 13 In the present study, we found that baicalin increased cell viability ( Figure 1A) and suppressed apoptosis (Figure 2A and B) of human fibroblast cells induced by UVB at 600 J/m 2 , the dose level high enough to caused fibroblast cells to undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are also other autophagy inducers reported in the context of neurotruama. Baicalin (7-D-glucuronic acid-5,6-dihydroxyflavone) is a major flavonoid in traditional Chinese medicinal herb isolated from the radix of Scutellaria baicalensis that was found to increase expression levels of LC3, Beclin 1, and p62 at 24 h following the weight-drop TBI model in mice [164]. Salubrinal is the selective phosphatase inhibitor of p-eIF2α.…”
Section: Therapeutic Potential Of Autophagy–lysosomal Pathway Modumentioning
confidence: 99%
“…Additionally, BAI administration increased the expression of GABA A receptor and α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor and decreased the activation of NLRP3 inflammasome in the hippocampus [ 21 ]. A number of studies have shown that BAI ameliorates various inflammatory diseases and prevents neurodegenerative diseases through various mechanisms [ 23 26 ], including suppression of oxidative stress, apoptosis, and inflammation, neurogenesis stimulation, and promotion of brain-derived neurotrophic factor (BDNF) expression. Moreover, the neuroprotective effects of BAI in neurological disorders like depressive-like behaviors [ 12 ] or oxidative stress injury of SH-SY5Y cells [ 27 ] have been linked to SIRT1 activation.…”
Section: Introductionmentioning
confidence: 99%